2010
DOI: 10.2135/cropsci2010.04.0192
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effects of Salinity and Mowing on Performance and Physiology of Bermudagrass Cultivars

Abstract: The effects of mowing management on salinity tolerance are not well understood. These effects were studied on turf quality, clipping yield, root mass, canopy photosynthetic rate (Pn), total nonstructure carbohydrate content (TNC), shoot reducing sugar content (RSC), and K+ and Na+ contents in shoots and roots of Tifgreen, Tifdwarf, and Tifway bermudagrass [Cynodon dactylon (L.) Pers.] cultivars using a hydroponic system. Increasing salinity resulted in a significant (p < 0.05) reduction in turf quality. Canopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 61 publications
6
28
1
Order By: Relevance
“…Estimation of visual coverage indicated that sparsely covered or bare soil areas in the northern and western parts of the park matched the areas with the highest salinity levels of 15 dS m -1 or higher. These observations support findings of Shaba (2010) and Marcum and Pessarakli (2006), who reported a threshold level of 15 dS m -1 at which bermudagrass drops below a rating of 6 for visual quality (Shahba, 2010) or reduces growth by 50% (Marcum and Pessarakli, 2006). Our observations also support findings of Xiang et al (2017) who documented a drop in live green cover for several bermudagrasses from greater than 80% at EC ≤ 15 dS m -1 to less than 50% at EC ≥ 15 dS m -1 .…”
Section: Model Calibration and Geospatial Distribution Of Saturated Psupporting
confidence: 91%
See 1 more Smart Citation
“…Estimation of visual coverage indicated that sparsely covered or bare soil areas in the northern and western parts of the park matched the areas with the highest salinity levels of 15 dS m -1 or higher. These observations support findings of Shaba (2010) and Marcum and Pessarakli (2006), who reported a threshold level of 15 dS m -1 at which bermudagrass drops below a rating of 6 for visual quality (Shahba, 2010) or reduces growth by 50% (Marcum and Pessarakli, 2006). Our observations also support findings of Xiang et al (2017) who documented a drop in live green cover for several bermudagrasses from greater than 80% at EC ≤ 15 dS m -1 to less than 50% at EC ≥ 15 dS m -1 .…”
Section: Model Calibration and Geospatial Distribution Of Saturated Psupporting
confidence: 91%
“…Soil texture of subsamples was determined using the hydrometer method (Gee and Or, 2002). Processed soil samples were analyzed for salinity (EC e ) (Rhoades, 1996); and concentrations of Na, Ca, and Mg using ion chromatography (Helmke and Sparks, 1996;Suarez, 1996). Sodium adsorption ratios of the samples were estimated from Ca, Mg, and Na concentrations (Essington, 2003).…”
Section: Calibration and Validation Of Soil Samplesmentioning
confidence: 99%
“…An increase in fructose content as a result of increased salinity was also found in wheat seedlings (Kerepesi & Galiba, ) and in creeping bentgrass seedlings (Qian & Fu, ). However, the levels of soil salinity documented in our study may not have created sufficient salt stress compared to what has been reported from greenhouse or growth chambers studies (Shahba, ; Shahba, Alshammary, & Abbas, ).…”
Section: Resultscontrasting
confidence: 83%
“…Goyal and Thind (2015) reported an enhanced sugar content in SWE treated rice, also Ciepiela et al (2016) found significant increases in TNC composition in fodder grass treated with Ecklonia maxima SWE. Salinity leads to the significant reductions of TNC as well as increases in reducing sugars in different turfgrasses (Qian and Fu, 2005; Shahba, 2010; Shahba et al, 2012). For example, Qian and Fu (2005) reported a reduction in TNC from 123.8 to 89.4 mg·g −1 dry wt when salinity increased from 0.2 dS·m −1 (tap water) to 15 dS·m −1 , respectively and they suggested that such reduction because TNC serves as a resource for the reduced sugars which normally increase under saline conditions.…”
Section: Discussionmentioning
confidence: 99%